Byakangelicin protects against carbon tetrachloride–induced liver injury and fibrosis in mice. Issue 15 (9th July 2020) - Li, Xiaohe; Shao, Shuaibo; Li, Hailong; Bi, Zhun; Zhang, Shanshan; Wei, Yiying; Bai, Jiakun; Zhang, Ruotong; Ma, Xiaoyang; Ma, Bowei; Zhang, Liang; Xie, Chunfeng; et al.
Abstract: Liver fibrosis is a disease caused by long‐term damage that is related to a number of factors. The current research on the treatment of liver fibrosis mainly focuses on the activation of hepatic stellate cell, in addition to protecting liver cells. byakangelicin has certain anti‐inflammatory ability, but its effect on liver fibrosis is unclear. This study aims to explore whether byakangelicin plays a role in the development of liver fibrosis and to explore its mechanism. We determined that byakangelicin has a certain ability to resist fibrosis and reduce liver cell damage in a model of carbon tetrachloride–induced liver fibrosis in mice. Thereafter, we performed further verification in vitro. The signalling pathways of two important pro‐fibrotic cytokines, transforming growth factor‐β and platelet‐derived growth factor, were studied. Results showed that byakangelicin can inhibit related pathways. According to the hepatoprotective effect of byakangelicin observed in animal experiments, we studied the effect of byakangelicin on 4‐HNE–induced hepatocyte (HepG2) apoptosis and explored its related pathways. The results showed that byakangelicin could attenuate 4‐HNE–induced hepatocyte apoptosis via inhibiting ASK‐1/JNK signalling. In conclusion, byakangelicin could improve carbon tetrachloride–induced liver fibrosis and liver injury by inhibiting hepatic stellate cell proliferation and activation and suppressing hepatocyte apoptosis.